The information system’s efficiency in the process of settling accounts tax - Qasem Kadem Hamed, Suhad Kashkoul Abid, (Opción, 2019)
The of t t y to nv t t t nfor t on y t ’ efficiency in the process of settling accounts tax via comparative qualitative research methods. As a result, the information system is characterized by the ability to store information through the provision of diverse information in more detail and enhance credibility, accuracy and impartiality in the results. In conclusion, subordination of auditors to pressure the owners of companies and then the ratification of accounts do not correspond to reality.